Hierarchical nanoporous Ge anodes for lithium-ion batteries via plasma-phase-fabricated Mg2Ge. Issue 23 (6th October 2022) - Fan, Zhen; Stevenson, Siobhan C.; Mungall, Alexander; Nishio, Akira; Szczęsny, Robert; Lin, Yan-Gu; Chen, Mark; Liu, Wei-Ren; Okada, Shigeto; Gregory, Duncan H
Abstract : Microwave-induced Mg plasma rapidly "deep reduces" GeO2 to Mg2 Ge, a precursor to bespoke hierarchical nanoporous Ge, which acts as a high-performance anode in lithium-ion cells. Abstract : Deep reduction-magnesiation of GeO2 to Mg2 Ge is achieved within 80 s via the microwave-induced-metal-plasma (MIMP) approach at 200 W in vacuo . A reaction mechanism can be proposed in which electrons function directly as reducing agents with germania. Almost simultaneously, interactions with electrons and Mg n + cations promote the ultrafast nucleation of Mg2 Ge. 3D hierarchical nanoarchitectures of Ge with coral-like structures and unique micro-meso-macro pore-distributions are then achieved by simple thermal dealloying of Mg2 Ge in air. With outstanding porosity of almost 90%, as anodes in lithium-ion batteries (LIBs), the Ge matrices are pulverisation-tolerant during cycling, accommodating volume changes and releasing stress. Reliable stability, excellent rate capability and consistently high gravimetric capacity 2–3 times that of graphite, are characteristic features of the anodes. Our method offers great scope for the sustainable, scaled-up production of nanoporous materials from oxides.